Executive Character and Tax Avoidance With Moderated Covid-19 Pandemic - Khoirunisa, Ulil Elma; Tjaraka, Heru (Owner : Riset dan Jurnal Akuntansi, 2024)
This study seeks to prove the influence of Executive Character on Tax Avoidance moderating with the effect of the COVID-19 pandemic. The population in this study is a Manufacturing Company on the Indonesia Stock Exchange from 2017 – 2022. The method used is the Moderating Regression Analysis with a total of 355 observations. This study shows that Executive Character has positive effects on Tax Avoidance, but the COVID-19 pandemic did not moderate the influence of Executive Character and Tax Avoidance. This study considers of COVID-19 pandemic as a factor that moderates the influence of Executive Character and Tax Avoidance